The use of ambulatory strategies for the diagnosis and treatment of obstructive sleep apnea in adults. (June 2013) - Chiner, Eusebi; Andreu, Ada L; Sancho-Chust, Jose N; Sánchez-de-la-Torre, Alicia; Barbé, Ferran
Obstructive sleep apnea (OSA) is a highly prevalent disorder associated with complications such as arterial hypertension, coronary heart disease, cerebrovascular disease and traffic accidents. Patients with untreated OSA consume more financial and healthcare resources and have higher mortality than those treated properly. The resources allocated for OSA are insufficient in some countries for such a prevalent disorder. This has given rise to a significant public health problem and a search for alternative strategies based on the ambulatory management. In the diagnostic process, portable monitors have been evaluated. Continuous positive airway pressure is the most effective treatment in OSA, but other forms of treatments have also been used (weight loss, oral appliances, surgery and so on). Ambulatory monitoring of the therapeutic modalities has been evaluated to enhance the care process and reduce costs compared with the conventional approach, without sacrificing efficiency. This review aims to highlight the most important advances in this field, analyzing the results of the main works to date, in order to assess the current situation and future research needs.